Within trophic level shifts in collagen–carbonate stable carbon isotope spacing are propagated by diet and digestive physiology in large mammal herbivores. Issue 8 (25th March 2018) - Codron, Daryl; Clauss, Marcus; Codron, Jacqueline; Tütken, Thomas
Abstract: Stable carbon isotope analyses of vertebrate hard tissues such as bones, teeth, and tusks provide information about animal diets in ecological, archeological, and paleontological contexts. There is debate about how carbon isotope compositions of collagen and apatite carbonate differ in terms of their relationship to diet, and to each other. We evaluated relationships between δ 13 Ccollagen and δ 13 Ccarbonate among free‐ranging southern African mammals to test predictions about the influences of dietary and physiological differences between species. Whereas the slopes of δ 13 Ccollagen –δ 13 Ccarbonate relationships among carnivores are ≤1, herbivore δ 13 Ccollagen increases with increasing dietary δ 13 C at a slower rate than does δ 13 Ccarbonate, resulting in regression slopes >1. This outcome is consistent with predictions that herbivore δ 13 Ccollagen is biased against low protein diet components ( 13 C‐enriched C4 grasses in these environments), and δ 13 Ccarbonate is 13 C‐enriched due to release of 13 C‐depleted methane as a by‐product of microbial fermentation in the digestive tract. As methane emission is constrained by plant secondary metabolites in browse, the latter effect becomes more pronounced with higher levels of C4 grass in the diet. Increases in δ 13 Ccarbonate are also larger in ruminants than nonruminants. Accordingly, we show that Δ 13 Ccollagen ‐carbonate spacing is not constant within herbivores, but increases by up to 5 ‰ across species with different diets and physiologies. Such large variation, often assumed to be negligible within trophic levels, clearly cannot be ignored in carbon isotope‐based diet reconstructions. Abstract : We compare collagen–carbonate stable carbon isotope relationships between mammal herbivores, carnivores, and omnivores. Whereas collagen–carbonate carbon isotope spacing is constant for carnivores and omnivores, carbonate 13 C‐compositions of herbivores increase with more C4 grass in the diet. These changes, which may amount to differences as large as 5 ppm, are consistent with theoretical predictions that relate carbon isotope compositions of skeletal matter to varying rates of methane production during fermentation in herbivores.